A Burning Question : "The Beveridge Report" (postcard) - Tattersall, A. A.
1942-12 1942 1940s 2 pages [Picture] A BURNING QUESTION. "BEWDLEY: BROWNHILL, BLACKBURN. "THE BEVERIDGE REPORT" Like the curate's egg, it is good in parts, and such as we get from those educated mainly in theoretical subjects. It lacks the practical education of the practical owners of our factories, foundries and staple productions, employing over 12,000,000 wage-earners. When there is no work, there are no wages, no matter what theorists and others may say. Let Parliament legislate, protect and help the owners of our factories, foundries and productions now and after the war, as they are the source of all our wealth and productive employment. If Parliament destroys the ambition and risks of the practical, experienced owners of our producing factories, foundries and staple productions, then we shall always have great unemployment and poverty. For Publication. A. A. TATTERSALL. (Over 60 years' experience in producing factories) 292/150.5/5/237